RANCANG BANGUN SISTEM INFORMASI ABSENSI KARYAWAN BERBASIS WEB (STUDI KASUS: PPKS MARIHAT DALU-DALU) - M. Reza Prayogge; Megawati Megawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The implementation of employee attendance at the Marihat Dalu-Dalu Oil Palm Research Center (PPKS) still uses a manual attendance system for each employee. This can cause problems in the future If the data is lost or If some employees will misuse the data. Therefore, to ensure that employee attendance is used effectively and efficiently within the company, it is necessary to have a web-based employee attendance system that can be managed and not abused consciously by some employees when designing an employee attendance system. with the creation of this employee attendance system design, the development examples used for this information system are waterfall software development and use UML (Unified Modeling Language) diagrams, namely use case diagrams, activity diagrams, deployment diagrams, component diagrams. to form the design of this employee attendance system makes it easier for companies to manage employee attendance systems so that they can be organized and effective and efficient so that employee attendance data is not misused and damaged or lost.